Cytopathogenic protein in filtrates from cultures of Propionibacterium acnes isolated from patients with Kawasaki disease. Issue 6608 (14th November 1987) - Tomita, S; Kato, H; Fujimoto, T; Inoue, O; Koga, Y; Kuriya, N
Abstract : Propionibacterium acnes may have a role in Kawasaki disease. Filtrates from cultures of P acnes isolated from cervical lymph node biopsy specimens and blood samples from patients with Kawasaki disease were studied and compared with samples from control subjects. After inoculation of human embryo liver cells with filtrates from the patients a cytopathogenic effect and vacuolation were seen. A specific cytopathogenic substance was found in only the filtrates of cultures from patients with Kawasaki disease; it was a protein of about isoelectric point 7.0 with a molecular weight of about 100, 000 daltons. The amount of IgG antibody to this cytopathogenic protein was measured by enzyme linked immunosorbent assay (ELISA) in serum samples taken from 63 patients in the acute phase of Kawasaki disease (mean 5.2 (SD 1.1) days after onset of illness), 45 in the subacute phase (mean 23.6 (3.3) days), and 51 in the convalescent phase (mean 18.5 (4.1) months) and from 102 control subjects matched for age. Titres of IgG antibody were significantly raised in patients with Kawasaki disease, particularly in the acute and subacute phases of the illness, compared with in the control subjects. Titres of IgG antibodies to cytopathogenic protein were found to be low in normal children below the age of 4 years but they increased with age thereafter. This may explain why outbreaks of Kawasaki disease, which is most common in children aged under 4, occur every three years.